Fundamentals of probability - Ghahramani, Saeed (Boca Raton : CRC press, 2024)
"This textbook provides a thorough and rigorous treatment of fundamental probability, including both discrete and continuous cases. The book's ample collection of exercises gives instructors and students a great deal of practice and tools to sharpen their understanding.
includes Appendix and index
Keywords: Conditional probability; Limit theorems; Random variables; Distribution (Probability theory)